Trk1-mediated potassium uptake contributes to cell-surface properties and virulence of Candida glabrata - Llopis-Torregrosa, Vicent; Vaz, Catarina; Monteoliva, Lucia; Ryman, Kicki; Engstrom, Ylva; Gacser, Attila; Gil, Concha; Ljungdahl, Per O; Sychrová, Hana (Scientific reports, 2019)
The absence of high-affinity potassium uptake in Candida glabrata, the consequence of the deletion of the TRK1 gene encoding the sole potassium-specific transporter, has a pleiotropic effect. Here, we show that in addition to changes in basic physiological parameters (e.g., membrane potential and intracellular pH) and decreased tolerance to various cell stresses, the loss of high affinity potassium uptake also alters cell-surface properties, such as an increased hydrophobicity and adherence capacity. The loss of an efficient potassium uptake system results in diminished virulence as assessed by two insect host models, Drosophila melanogaster and Galleria mellonella, and experiments with macrophages. Macrophages kill trk1Δ cells more effectively than wild type cells. Consistently, macrophages accrue less damage when co-cultured with trk1Δ mutant cells compared to wild-type cells. We further show that low levels of potassium in the environment increase the adherence of C. glabrata cells to polystyrene and the propensity of C. glabrata cells to form biofilms.
Keywords: Candida glabrata; buněčná membrána; draslík; Drosophila melanogaster; proteiny přenášející kationty; povrchové vlastnosti; Humans; Cation Transport Proteins; Potassium; Hydrophobic and Hydrophilic Interactions; makrofágy; Virulence; Ion Transport; Cell Adhesion; lidé; zvířata; virulence; THP-1 buňky; buněčné linie; Cell Line; biofilmy; Moths; Potassium-Hydrogen Antiporters; můry; iontový transport; Animals; buněčná adheze; Cell Membrane; Macrophages; Membrane Potentials; membránové potenciály; draslíko-vodíkové antiportéry; regulace genové exprese u hub; THP-1 Cells; Surface Properties; hydrofobní a hydrofilní interakce; Gene Expression Regulation, Fungal; Biofilms